The palaeoredox condition and morphological variation of microbialites from the Nama Group, South Africa - Wilton, Aidan (Department of Geological Sciences, 2024)
Microbialites are the fossilised traces of microbial communities and are present in the rock record since the Paleoarchean, 3.5 billion years ago, making microbialites some of the earliest direct evidence for life on Earth. Microbialites exhibit a wide variety of macrostructures and fabrics, including laminated sheets, domes and clotted thrombolites, and formed under a range of conditions. Microbialites also vary on fine scales whereby individual layers in some cases vary within a single microbialite. The ubiquity of microbial reefs across the Precambrian means they were some of the most abundant deposits during major developments in Earth's history, namely the inception of photosynthesis, the oxygenation of the atmosphere and oceans, the development of the earliest metazoans and the origin of skeletonization. While Earth's atmosphere has contained oxygen since the GOE, the oceans only became persistently oxic during the mid-Palaeozoic. Oscillatory redox conditions occurred throughout the Cryogenian and Ediacaran Periods and the early Palaeozoic Era before this stability was reached. While oxic surface waters were present throughout the Proterozoic, there are open questions as to the maximum dissolved oxygen levels, and where oxic waters were located. Microbial reefs, typically composed of photosynthetic cyanobacteria, could have played a vital role in shaping this oxygen landscape. It is possible that cyanobacteria within the reefs created local oxygen oases within a generally low oxygen environment. Here, I test this hypothesis using a suite of microbialites from a section of the Nama Group that crops out in the Northern Cape, South Africa. I have studied the texture and mineralogy using XRD, SEM, petrography, and polished surfaces. I have also analysed high-resolution rare-earth element patterns from microdrilled microbial laminae to study local redox conditions. Analysis of the mesostructure and microstructure of the microbialites indicates that they were columnar stromatolites that grew into an extensive reef of domal stromatolites within the subtidal zone. Small-scale spatiotemporal feature variations indicate there was widespread turbulence across the reef, potentially indicating rapid fluctuations in water depth or the creation of topographic heterogeneity by the reef. The laminae of the microbial material are composed of micritic calcite peloids, while the intercolumn material is largely microspar calcite. The presence of peloids coupled with the ubiquitous columnar growth patterns suggest an association with microbial activity. In concert with the proposed relatively shallow water depositional environment, it is likely that photosynthetic cyanobacteria are the primary microbes that created these structures. The REE data record primary seawater compositions and are in line with bulk rock analysis from the Nama Group. However, there are no cerium anomalies, suggesting these microbial reefs grew in anoxic waters. This is contrary to the cyanobacterial affinities of the microbialites as well as the presence of in-situ animal fossils in similar microbial reefs in other parts of the Nama Group. We propose three main models to reconcile these observations. First, the microbial communities may not have included oxygenic cyanobacteria, and the micro- and macro-environment surround the reef may have been anoxic. Second, the microbial reefs may have been oxic micro-environments, but this may not be reflected in the REE patterns due to microbial influence on the partitioning behaviour of Ce, or timescales of oxygen production that were much shorter than depositional timescales. Thirdly, the REE may reflect the surrounding water column, rather than the oxic reef environment, if the carbonate was trapped and bound, rather than precipitated in situ.